Reductive Behavior of [Fe2(CO)4(κ2‐dmpe)μ‐(SCH2)2NBn]: Effect of Symmetrization on the Rotated Conformation in FeI‐FeI Models of [2Fe]H Subsite of [Fe‐Fe]H2ases1. Issue 22 (4th July 2014) - De Gioia, Luca; Elleouet, Catherine; Munery, Sabrina; Pétillon, François Y.; Schollhammer, Philippe; Talarmin, Jean; Zampella, Giuseppe
Abstract: The reduction of the compound [Fe2 (CO)4 (κ 2 ‐dmpe)μ‐(SCH2 )2 NBn] [dmpe = 1, 2‐bis(dimethylphosphino)ethane], which is considered as an Fe I ‐Fe I model of the [2Fe]H subsite of [Fe‐Fe]H2 ases with a rotated conformation in the solid state, was investigated by cyclic voltammetry. Under reductive conditions, [Fe2 (CO)4 (κ 2 ‐dmpe)μ‐(SCH2 )2 NBn] undergoes electron‐transfer‐catalyzed isomerization to afford an isomer featuring a bridging diphosphine [Fe2 (CO)4 (μ‐dmpe)μ‐(SCH2 )2 NBn]. Comparison of the crystallographic structures of the two isomers affords unique and direct experimental evidence that dissymmetrical coordination of the chelate ligand is required to promote the rotated conformation at one iron atom in this compound. DFT calculations were performed to rationalize this isomerization process and the slightly distorted structure of [Fe2 (CO)4 (μ‐dmpe)μ‐(SCH2 )2 NBn]. The symmetrization of the coordination sphere results in the disruption of the agostic interaction that stabilized the rotated isomer. Abstract : Electrosynthesis, through an electron‐transfer‐catalyzed process, and structural characterization of the symmetrical complex [Fe2 (CO)4 (μ‐dmpe)μ‐(SCH2 )2 NBn] [dmpe = 1, 2‐bis(dimethylphosphino)ethane] afford straight experimental evidence that desymmetrization is required to promote an inverted pyramidal conformation in this class of model compounds of the [2Fe]H subsite of [Fe‐Fe]H2 ases.